Fabrication of MoS2@SnO2-SnS2 composites and their applications as anodes for lithium ion batteries. (December 2018) - Li, Haojie; Su, Qingmei; Kang, Jinwei; Feng, Huagui; Huang, Ping; Feng, Miao; Huang, Min; Du, Gaohui
Graphical abstract: Highlights: The MoS2 @SnO2 -SnS2 composites were successfully fabricated. The composites show long-term cycling performance used as anode for LIBs. The superior performance ascribes to the synergistic effect between MoS2 and SnO2 . Abstract: Sn-based anode for lithium-ion batteries (LIBs) has been received extensive concern, due to its high theoretical specific capacity. However, its poor stability induced by serious volume changes during charge/discharge process limits its application. MoS2 possesses a 2-dimisional (2D) graphene-like layered structure facilitates lithium ions insertion and extraction and can be served as the buffer to alleviate the volume variation. Unfortunately, 2D MoS2 nanosheets are highly susceptible to stacking/restacking during cycles, which is fatal to their capacity retention. Herein, a novel MoS2 @SnO2 -SnS2 composite has been designed and fabricated via a two-step simple hydrothermal route. Due to the synergistic effect between the ultrathin MoS2 nanosheets and the SnO2 -SnS2 nanosheets, the MoS2 @SnO2 -SnS2 composite exhibits excellent electrochemical performance as anode for LIBs.